PERAN IBU BEKERJA DALAM MENANAMKAN KEPERCAYAAN DIRI PADA ANAK USIA 4-6 TAHUN - Asla De Vega (Program Studi Pendidikan Islam Anak Usia Dini, 2022)
Early childhood is an individual who is experiencing a sensitive period in forming the best possible personality which is very influential in his adult age. The need for parental assistance in educating children, especially mothers. Working mothers have multiple responsibilities such as taking care of the household and working outside the home. For this reason, the role of working mothers is important so that their responsibilities are resolved. This article is the result of a study/library that aims to find out how the role of working mothers in instilling children's confidence. This study examines several reputable research articles as well as supporting books in this literature study. Based on the results of the analysis that the level of confidence of children aged 4-6 years who are cared for by working mothers depends on the time management and parenting used.